Highly dispersive solitary wave solutions of perturbed nonlinear Schrödinger equations - Kudryashov, Nikolay A. (Applied mathematics and computation, 2020)
Hierarchy of the perturbed nonlinear Schrödinger equations is considered. Nonlinear differential equations of this hierarchy contain higher orders and can be used for description of highly dispersive optical solutions. A new approach for finding solitary wave solutions of high-order nonlinear differential equations is presented. This approach allows us to significantly simplify symbolic calculations. The main idea of the method is that we use expressions of the dependent variable and its derivatives in the differential equation the polynomial form of the solitary wave. We find optical solitons with high dispersion order for nonlinear perturbed Schrodinger equations of the fourth, sixth, eighth, tenth and twelfth orders.